Designing of an office appliance system using temperature sensor & micro controller for efficient use of electricity - Das, Rajat; Bhuiyan, Mafruzul Murshed; Ahmed, Anika Amin; Hassan, Md. Mahadi (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.